DIỄN BIẾN HÀM LƯỢNG PCDDs/PCDFs VÀ dl-PCBs TRONG KHÔNG KHÍ THEO MÙA Ở MỘT KHU VỰC NỘI THÀNH GIAI ĐOẠN 2012-2020 - Trịnh, Khắc Sáu; Nghiêm, Xuân Trường; Trần, Đình Phiên; Nguyễn, Đức Thắng; Nguyễn, Thu Lý (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
SEASONAL AIR MONITORING OF PCDDs/PCDFs AND dl-PCBs IN A RESIDENTIAL URBAN AREA BETWEEN 2012-2020The ambient air monitoring of PCDDs/PCDFs and dl-PCBs using passive air samplers in a residential urban area in Hanoi between 2012-2020 was deteminated. The seasonal variations of PCDD/PCDF and dl-PCB levels in ambient air in three periods: between Spring 2012 and Autumn 2015, from Winter 2015 to Autumn 2018, and between Winter 2018 and Autumn 2020 are similar to a V-shape with the highest peak in winter, then decreasing gradually in spring, bottoming in summer and rising again in autumn. The upward temporal trends of PCDD/PCDF and dl-PCB pollution, and total TEQD/F&DL, total TEQD/F and total TEQDL has been confirmed over time. The concentrations of total PCDFs were dominant and were approximately 1.0 to 9.3 times higher and 2.4 times higher on average than total PCDDs. Total dl-PCBs were 5.8 to 38 times higher and 17 times on average higher than the total toxic PCDDs/PCDFs. The PCDD/PCDF congeners contributed 83% to 95% of the total TEQ value. The phenomenon of temperature inversion not only causes seasonal air pollution but also increases the concentration of PCDDs/PCDFs and dl-PCBs with a narrower range but at a higher average levels.